PENGARUH KUALITAS JASA DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PEGADAIAN (Studi Kasus Upc Sawah Lebar ) - Ida ayu Made Er Meytha Gayatri; Eska Prima Monique Damarsiwi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This type of research is a quantitative study in which sampling uses incidental sampling techniques and the number of samples 30 respondents. The technique of answering data using a questionnaire. The data obtained were analyzed using SPSS, with analysis test multiple regression, double correlation analysis and statistical tests (t test, and F test,). The results of the study indicate that simultaneously, service quality and trust variables, together affect loyalty in Upc Sawah Lebar. While partially the service quality variable (X1) significantly influences customer loyalty at Upc Sawah Lebar with a sig value of 0.012. The trust variable (X2) also has a significant effect on customer loyalty at Pegadaian Upc Sawah Lebar with a sig value of 0.21. While the coefficient of determination (R2) of 52.1 for Upc Sawah Lebar means that the contribution of an independent variable explains or influences the dependent variable by 52.1%, while the remaining 47.9% is influenced by other variables not examined in this study. Key Words: service quality, trust